A three-dimensional smoothed particle hydrodynamics dispersion simulation of polydispersed sediment on the seafloor using a message passing interface algorithm - Tran-Duc, Thien; Phan-Thien, Nhan; Khoo, Boo Cheong (Physics of fluids (1994), 2019)
Technical activities on seafloor for harvesting polymetallic nodules result in a displacement of a large amount of sediment, which is convected away from the site by the underlying currents and turbulent diffusion, with a possible impact on the benthic communities living in the neighborhood. To better understand the dispersion mechanism of the resuspended sediment, a smoothed particle hydrodynamics technique augmented by a message passing interface parallel algorithm to address the intensive demand on the three-dimensional simulations is developed. Our numerical results show that the resuspended sediment would occupy a downstream area extending to about 5 km, for a nominal current speed of 5 cm/s. The evolution of the sediment plume occurs mainly along the current direction, while the turbulent diffusion disperses the sediment laterally. Coarse sediment particles are found to return to the seafloor fairly quickly after being resuspended, while fine particles are more persistent in the suspended state and travel much further downstream. In 900 tons of sediment resuspended for 18 h, 318 tons have returned to the bottom at the end of the simulation period. The majority of the deposited sediment is composed of coarse sediment particles (d > 60 μm), and almost half of the deposited sediment is distributed within the harvesting region. The sediment deposition rate reaches up to 48% of the resuspension rate and is still rising after 18 h. The horizontal turbulent diffusivity, which is supposed to be weak at the ocean bottom, does not have any obvious influence on the dispersion of the resuspended sediment; it only slightly reduces the deposition rate.